Safety and Reliability Analysis of Reconfigurable Battery Energy Storage System - Helin Xu; Lin Cheng; Daniyaer Paizulamu; Haoyu Zheng (Batteries)
Lithium-ion batteries (LIBs) are widely used in electric vehicles (EVs) and energy storage systems (ESSs) because of their high energy density, low self-discharge rate, good cycling performance, and environmental friendliness. Nevertheless, with the extensive utilization of LIBs, incidents of fires and explosions resulting from thermal runaway (TR) have become increasingly prevalent. The resolution of safety concerns associated with LIBs and the reduction in operational risks have become pivotal to the operation and control of ESSs. This paper proposes a model for the TR process of LIBs. By simplifying the modeling of TR reactions, it is possible to calculate the starting temperature of the battery self-heating reaction. Subsequently, this paper puts forth an operational reliability evaluation algorithm for a reconfigurable battery energy storage system (BESS). Finally, this paper develops a control algorithm for reliability improvement, with the objective of ensuring safe and stable control of the ESS.